(1063) Trends of Development and Some Topical Problems in Czechoslovak Agriculture اتجاهات التنمية وبعض المشاكل الراهنة في الزراعة التشيكوسلوفاكية - Ing. V. Lohr. (INP., 2020)
This study examines the evolution of agricultural production over the past twenty-five years, with a particular focus on the transition from individual peasant farming to cooperative systems. Emphasis is placed on the policy initiatives undertaken during the 1940s–1960s, which aimed to rationalize and modernize the agricultural sector through collective organization and improved labor productivity. The analysis considers the challenges in defining developmental stages, the declining role of manual labor per unit of output, and the importance of historical context in shaping future agricultural goals. Key areas of investigation include the dynamics of production transformation, the role of production factors in enhancing labor efficiency, and the issue of territorial differentiation. The report concludes that, despite past efforts, agricultural development has not kept pace with national needs or potential, highlighting the necessity for strategic reforms to close the gap with more advanced economies.